2011
DOI: 10.1590/s0102-86502011000800011
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic islet allograft in spleen with immunossuppression with cyclosporine. Experimental model in dogs

Abstract: PURPOSE: To study the functional behavior of the allograft with immunosuppression of pancreatic islets in the spleen. METHODS: Five groups of 10 Mongrel dogs were used: Group A (control) underwent biochemical tests; Group B underwent total pancreatectomy; Group C underwent total pancreatectomy and pancreatic islet autotransplant in the spleen; Group D underwent pancreatic islet allograft in the spleen without immunosuppressive therapy; Group E underwent pancreatic islet allograft in the spleen and immunosuppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The respect due to this organ because of its importance in the physiopathology of many diseases has favored the development of multiple operations aiming at the preservation of the spleen, with a consequent reduction of sepsis rates and of postoperative hematologic disorders 19 . Total splenectomy, which used to be extensively indicated in the past, is being progressively replaced with spleen-conserving procedures such as spleen suture, partial splenectomy, subtotal splenectomy or autogenous spleen tissue implant after spleen removal 18,20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…The respect due to this organ because of its importance in the physiopathology of many diseases has favored the development of multiple operations aiming at the preservation of the spleen, with a consequent reduction of sepsis rates and of postoperative hematologic disorders 19 . Total splenectomy, which used to be extensively indicated in the past, is being progressively replaced with spleen-conserving procedures such as spleen suture, partial splenectomy, subtotal splenectomy or autogenous spleen tissue implant after spleen removal 18,20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…Whereas canine diabetes mellitus has been described as an ideal preclinical model for T1DM in people, most islet transplant studies were actually carried out in healthy research animals that underwent pancreatectomy or chemically induced diabetes, where success would be expected to be higher than in clinical patients with autoimmune induced beta cell destruction. Nonetheless, a vast amount of information has been assembled in over 40 studies involving canine islet isolation, preservation, or transplantation (Table ) . A small number of recent studies have even shown some promise in resolution of spontaneous diabetes in client‐owned dogs (Table ) …”
Section: Pancreatic Islet Transplantationmentioning
confidence: 99%